How are partners used in the search for innovations? A systematic review - Hemel, Stefan (Cranfield University, 2013)
The importance of search partnerships has grown as a mode to search for innovations. However, in spite of this development, notions of open innovation combined with new propositions to change the search process in favour of sustainability have unravelled a need to take stock of the existing literature of search partnerships and the aims that these partnerships follow. This review addresses this shortcoming and synthesises the literature on search partnerships to analyse the current state of knowledge to deliver future research opportunities. A systematic review process was adopted by means of a set a set of pre-defined stages. These stages included the formulation and positioning of the review question within the larger literature domains, a systematic research process which included the adoption of search strings, relevance and quality appraisal criteria, as well as a stock-taking process of descriptive and thematic features, which followed the logic of prescriptive synthesis. This process led to a representative sample of 73 articles which were analysed subsequently. The tentative findings reveal that the literature is underpinned by a combination of theories linking to evolutionary or transaction-based understandings of search partnerships. Also, six conditions were found to drive search partnerships and when they are likely to form. Moreover five interventions were identified that relate to the use of search methods, boundary spanning activities, and the number, type and involvement levels with the partner. Finally search partnerships have been found to yield five outcomes: partnerships, and various types of innovations, higher social goals, as well as market knowledge. By combining contexts, interventions, and outcomes, research opportunities are identified that should inform future reviews, including the need for more research in sustainability-led search partnership contexts and a better understanding of search strategy configurations in relation interventions used and anticipated search partnership outcomes obtained.
Keywords: Search partnerships; open innovation; alliances; search strategies; systematic review